Evaluation of the Clinical Outcome of Metastatic Breast Cancer Patients with Negative and Positive Circulating Tumor DNA: A Systematic Review and Meta-analysis - Seyedeh Solmaz Riazi; Maryam Fathi (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2024)
Background and aim: The present study was conducted with the aim of evaluating the clinical outcome of metastatic breast cancer patients with negative and positive circulating tumor DNA. Material and methods: Searching international databases PubMed, Web of Science, Scopus, Science Direct, Web of Knowledge, EBSCO, Wiley, ISI, Elsevier, Embase databases, and Google Scholar search engine based on PRISMA 2020-27-item checklist and keywords Related to the objectives of the study, it was carried out from 2019 to February 2024. a model with fixed effect and inverse-variance method was used. All statistical analyses are done using STATA/MP software. v17 was done considering the significance of less than 0.05. Results: Six studies were selected according to the inclusion criteria. Compared with patients with negative ctDNA, those with positive ctDNA had a higher risk for progression-free survival and overall survival (HR 2.02, 95% CI 0.71-3.33; P-value < 0.001) and (HR 2.78, 95% CI 1.47-4.10; P-value < 0.001), respectively. Conclusions: In metastatic breast cancer patients, it was individually and jointly associated with progression-free survival and overall survival-positive circulating tumor DNA.